Spectrum and frequencies of mutations in the GJB2 (Cx26) gene among 156 Czech patients with pre-lingual deafness - Seeman, P; Malíková, M; Rasková, D; Bendová, O; Groh, D; Kubálková, M; Sakmaryová, I; Seemanová, E; Kabelka, Z (Clinical genetics, 2004)
Mutations in the gene gap junction beta 2 (GJB2), the gene for the connexin 26, are the most common cause of pre-lingual deafness worldwide. The mutation 35delG within GJB2 is prevalent in Europe. To date, there are no data about GJB2 mutation spectrum and frequencies from the Czech population. We investigated and report here the spectrum and frequencies of mutations in the GJB2 gene among 156 unrelated, congenital deafness Czech patients. Allele-specific polymerase chain reaction, together with fluorescent fragment analysis, were used for the detection of the 35delG mutation. The entire coding region of the GJB2 was directly sequenced in all patients who were not homozygous for the 35delG. No pathogenic mutation was detected in 51.9% of patients. At least one pathogenic mutation was found in 48.1% of patients, and both pathogenic mutations were detected in 37.8% of patients. Single mutations in a heterozygous state were detected in 10.3% of patients. The mutation 35delG accounts for 82.8% of detected disease mutations, Trp24stop accounts for 9.7% of pathogenic alleles and was found in patients with gypsy heritage. Mutation 313del14 accounts for 3.7% of pathogenic alleles. The frequency of 35delG heterozygotes in the Czech Republic is 1 : 29.6. Testing for only the three most common mutations would detect over 96% of all pathogenic alleles in the Czech Republic.
Keywords: konexiny; Mutation; Cohort Studies; Connexin 26; DNA primery; Humans; Czech Republic; Česká republika; kohortové studie; DNA Primers; Sequence Analysis, DNA; DNA Mutational Analysis; mutační analýza DNA; hluchota; sekvenční analýza DNA; Deafness; Connexins; mutace; lidé; konexin 26